Multiresidue Analysis of Organic UV Filters and UV Stabilizers in Fish of Common Consumption - Sandra Gimeno-Monforte; Sarah Montesdeoca-Esponda; Zoraida Sosa-Ferrera; José Juan Santana-Rodríguez; Óscar Castro; Eva Pocurull; Francesc Borrull (Foods, 2020)
Fish species can bioaccumulate different pollutants present in the marine environments and incorporate them into the trophic chain. In this work, the occurrence of organic ultraviolet (UV) stabilizers and filters in different species of fishes of high consumption has been studied. A multiresidue method based on microwave-assisted extraction and ultra-high performance liquid chromatography with mass spectrometry detection was developed and then it was applied to nine fish species from markets in the Canary Islands and Catalonia (Spain). Three UV filters (BP-3, OC and BM-DBM) and two stabilizers (UV-328 and UV-329) were found in some of the studied species, in concentrations ranging between 0.067 and 0.683 µg g−1 dry weight (dw). BP-3 (UV filter) was the most frequently detected compound, followed by UV-329 (UV stabilizer). Thunnus thynnus was the most heavily polluted species, with a concentration of 1.201 µg g−1 dw as the sum of all measured compounds.